Pembelajaran Matematika Model Reog Meningkatkan Kreatifitas Belajar Siswa SMPN di Kabupaten Pacitan - Khoirul Qudsiyah; Tika Dedy Prastyo (Jurnal Penelitian Pendidikan, 2014)
Creativity of students in learning mathematics is identically with their efforts to actively learnby themselves. As an alternative, REOG model is expected to encourage students in beingmore active and able to think creatively in solving mathematical problems. Students areinvited for rationalizing mathematical problems, elaborating, organizing understanding, andStyling completion based on their own creativity. The activity is a key for students to knowmathematics through other models of teaching and learning activities.